On the general form of jump conditions for thin irregular shells - Makowski, J.; Pietraszkiewicz, W.; Stumpf, H. (Archives of Mechanics, 1998)
The paper deals with the nonlinear theory of thin shell structures in the presence of irregularities in geometry, deformation, material properties and loading. The irregular shell is modelled by a reference network being a union of piecewise smooth surfaces and space curves, with various fields satisfying relaxed smoothness, differentiability, and regularity requirements. Transforming the virtual work principle postulated for the entire reference network, the corresponding local field equations and side conditions (boundary and jump conditions) are derived. It is shown that no more than four static and work-conjugate kinematic jump conditions can correctly be formulated whenever the shell deformation is assumed to be entirely determined by deformation of the reference network capable of resisting to stretching and bending. This assumption includes various special formulations of the Kirchhoff-Love type theory of elastic shells, as well as their substantial generalizations accounting for finite strains and inelastic deformations.